PENGARUH HUKUM ADAT TOBA ATAS STATUS PERKAWINAN SUKU BATAK TOBA - Michael Gabriel Halomoan Angkat; Rosmalinda Rosmalinda (JOURNAL SAINS STUDENT RESEARCH, 2024)
The focus of this study aims to look at marriages in the Toba Batak community who marry between clans, which is a factor caused by globalization. The exogamous marriage process (marriage outside the clan group) is a characteristic of the marriage process of the Toba Batak community so that the Toba Batak community strictly prohibits marriages within the clan because marriages within the clan are considered incest. This research is a type of normative-empirical legal research (applied legal research). The research specifications used are descriptive analytical, namely research intended to look at humans and other conditions/symptoms that are occurring. The results of the research show that the Toba Batak traditional community, whose patrilineal kinship system and exogamous marriage system, has a customary provision that members of the same clan are prohibited from marrying, because the marriages they carry out are still related by blood or one ancestor. The prohibition on intermarriage between clans is absolute so that anyone who violates this prohibition must receive sanctions of their choice. Some of the sanctions include, namely, being expelled from family ties, couples who carry out inter-clan marriages are no longer related to the extended family and are not allowed to participate in all traditional activities, the couple is not allowed to remain in their residence within the scope of indigenous people, but were exiled because they were considered a disgrace within the Batak traditional community. It is recommended that parents teach or educate their children from a young age to understand the Toba Batak traditional rules, so that when they grow up, children who are going to get married can choose a life partner who does not conflict with Toba Batak customs and for Toba Batak traditional leaders to always provide customary understandings, especially regarding the prohibition of intermarriage, which is inherent and ingrained in the life of the Toba Batak traditional community so as to straighten out the understanding of the next generation of descendants of the Toba Batak traditional community with Batak culture.